2020
DOI: 10.1117/1.nph.7.1.015007
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition-assisted long-term potentiation in the prefrontal-amygdala pathway via suppression of somatostatin-expressing interneurons

Abstract: Significance: Natural brain adaptations often involve changes in synaptic strength. The artificial manipulations can help investigate the role of synaptic strength in a specific brain circuit not only in various physiological phenomena like correlated neuronal firing and oscillations but also in behaviors. High-and low-frequency stimulation at presynaptic sites has been used widely to induce long-term potentiation (LTP) and depression. This approach is effective in many brain areas but not in the basolateral a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…SOM+ interneurons are also a critical part of the amygdala anxiety circuit, and changes in their excitability influence anxiety-like behaviors (reviewed by Prager et al [ 35 ], Babaev et al [ 37 ], Robinson and Thiele [ 57 ]). Dendritic inhibition via SOM+ interneurons efficiently gate generation of dendritic Ca+ signals and plasticity induction [ 58 60 ]. Therefore, the increase in SOM-mediated dendritic inhibition as an indirect consequence of lost GluK1 KAR function could contribute to the altered threshold for plasticity in LA, observed after early life stress [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOM+ interneurons are also a critical part of the amygdala anxiety circuit, and changes in their excitability influence anxiety-like behaviors (reviewed by Prager et al [ 35 ], Babaev et al [ 37 ], Robinson and Thiele [ 57 ]). Dendritic inhibition via SOM+ interneurons efficiently gate generation of dendritic Ca+ signals and plasticity induction [ 58 60 ]. Therefore, the increase in SOM-mediated dendritic inhibition as an indirect consequence of lost GluK1 KAR function could contribute to the altered threshold for plasticity in LA, observed after early life stress [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently it has been demonstrated that the spiking of amygdalar principal neurons evoked by synaptic excitation could be suppressed by activation of SST inhibitory cells (Wolff et al, 2014 ). This activation can even lead to gating long-term potentiation, at least at excitatory synapses of prefrontal-basal amygdala afferents (Ito et al, 2020 ).…”
Section: Dendritic Inhibitionmentioning
confidence: 99%
“…In the BLA, SOM INs have been implicated in modulating external inputs 45 , plasticity 69 , and feedforward 70 and feedback inhibition 71 . Here, we describe a novel role of SOM INs in gating activity of CCK INs to modulate BLA network synchronization.…”
Section: Discussionmentioning
confidence: 99%